1974
DOI: 10.1159/000231199
|View full text |Cite
|
Sign up to set email alerts
|

Three Pregnancy-Associated Human Plasma Proteins: Purification, Monospecific Antisera and Immunological Identification

Abstract: Three human pregnancy-associated plasma proteins (PAPPs), which were detected only during pregnancy with appropriately absorbed antisera to pregnancy plasma, were purified from third trimester plasma. The authors employed combinations of sequential DEAE-cellulose and hydroxylapatite chromatography; Sephadex G-100, G-200 and Sepharose 6B gel filtration; isoelectric focusing; and/or ammonium sulfate salting out. Each final product was shown to contain only one PAPP, to be immunologically free of most normal plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…The four pregnancy protein immune systems in the crossed antibody immunoelectrophoresis had been identified earlier in tests with the purified PAPP's (2,3). In the present study, the precipitin hills were readily identified on the basis of their electrophoretic mobilities, their times of appearance, and the characteristics of the precipitin lines.…”
Section: Methodssupporting
confidence: 54%
See 3 more Smart Citations
“…The four pregnancy protein immune systems in the crossed antibody immunoelectrophoresis had been identified earlier in tests with the purified PAPP's (2,3). In the present study, the precipitin hills were readily identified on the basis of their electrophoretic mobilities, their times of appearance, and the characteristics of the precipitin lines.…”
Section: Methodssupporting
confidence: 54%
“…In fact, Bohn has recently preferred to designate them as acute phase proteins (35). In contrast, all of the PAPP's described here appear to be generally pregnancy specific, since none of them have been detected by the methods used in nonpregnant normal male or female plasma, in plasma from patients with a variety of cancers not derived from the trophoblast, or in women receiving hormonal contraceptives (3).…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Pregnancy Associated Plasma Protein (PAPP-A) is an important glycoprotein found in maternal blood that increases as pregnancy progresses [1], although it is not specific to pregnancy [2,3]. In pregnancy, PAPP-A is principally expressed in the syncytiotrophoblast of the placenta, which forms the main source of circulating maternal PAPP-A [4][5][6].…”
Section: Introductionmentioning
confidence: 99%